Program English Literacy: Pengenalan Membaca dan Menulis Bahasa Inggris Dasar bagi Siswa Sekolah Dasar - Hastini; Fiisyatin Rodiah; Iskandar; Sri Fitriwati Andi Patangai (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
English literacy serves as an essential foundation in preparing the younger generation to face the challenges of global communication, yet the reality in the field reveals that many elementary school students in Indonesia have yet to develop these foundational skills adequately. Fifth-grade students at SDN Bulubonggu, Pasangkayu Regency, faced significant limitations in basic English reading and writing due to the lack of innovative teaching methods and limited instructional media. As a solution, the English Literacy Program was implemented as a community service activity designed to introduce foundational English literacy skills to students while providing an alternative pedagogical model for teachers. The activity was conducted in a one-day session using an integrated literacy approach that combined interactive visual media and educational games. The results demonstrated significant improvement in basic vocabulary comprehension, reading simple words and sentences, and writing letters and words in English, while also enhancing student enthusiasm and broadening teachers' pedagogical repertoire.